2019
DOI: 10.20546/ijcmas.2019.801.190
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Studies in Bell pepper (Capsicum annuum L. var. grossum) under Mid Hill Conditions of Solan District of Himachal Pradesh, India

Abstract: cooked as vegetable or widely used in stuffings, bakings, pizza making, and preparation of soups and stews for imparting flavour, aroma and colour. Bell peppers are available in different colours viz., yellow, red, green, purple and orange. These plump, bell shaped vegetables were cultivated more than 900 years ago in South and Central America and were given the name 'pepper' by the European colonizers of North America. These can easily grow in different types of climate. Sweet peppers are a great

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…Sharma et al (2010) found that fruit length, fruit diameter and number of fruits per plant revealed significant positive correlation with fruit yield per plant. Thakur et al (2019) found that highly significant and positive correlation of yield per plant with number of fruits per plant, fruit weight and number of primary branches.…”
Section: Phenotypic Correlation Coefficients Among the Pepper Studied Traitsmentioning
confidence: 96%
“…Sharma et al (2010) found that fruit length, fruit diameter and number of fruits per plant revealed significant positive correlation with fruit yield per plant. Thakur et al (2019) found that highly significant and positive correlation of yield per plant with number of fruits per plant, fruit weight and number of primary branches.…”
Section: Phenotypic Correlation Coefficients Among the Pepper Studied Traitsmentioning
confidence: 96%
“…El pimiento (Capsicum annuum L.) es una planta de la familia de las solanáceas, cuyo origen es Centroamérica y Suramérica, y que constituye una hortaliza de amplia importancia económica a nivel mundial [1] [2] [3]. Este cultivo presenta una planta que crece en forma indeterminada, que puede alcanzar unos 2m o más de altura [4], y cuyos frutos maduros pueden ser de color amarillo, rojo, verde, morado o anaranjado [5].…”
Section: Introductionunclassified
“…El pimiento se consume generalmente crudo, cocido como hortaliza, o para rellenar comidas, y en la preparación de sopas y comidas al vapor, para dar aroma, sabor y color; los pimientos están disponibles en diferentes colores, tales como amarillo, rojo, verde, morado y anaranjado [3].…”
Section: Introductionunclassified
“…Varios investigadores han estudiado la correlación existente entre diferentes características en pimiento [3] Se ha informado de una investigación sobre la correlación entre la densidad de siembra y las variables de rendimiento en chile dulce bajo invernadero en Costa Rica, en una variedad de frutos de forma cónica [38]. Sin embargo, no se conocen estudios en Costa Rica sobre la correlación entre dichas variables, en el cultivo de pimiento de frutos de forma cuadrada producido bajo invernadero.…”
Section: Introductionunclassified